Laporan Kasus: Pasak Fiber Prefabricated dengan Crown Zirconia pada Gigi Anterior - Ratih Delio Rakhmadian; Meidi Kurnia Ariani (Lembaga Bale Literasi, 2025)
Teeth that have undergone root canal treatment, whether diagnosed with pulp necrosis or irreversible pulpitis, have lost significant hard tissue structure due to caries. Post-root canal restoration generally involves additional reinforcement inserted into the root canal. This treatment is called post treatment, followed by crown placement. Based on the manufacturing method, posts are divided into two types: custom-made posts and prefabricated posts. Prefabricated posts are the most commonly used because they are made of fiber and offer several advantages. The advantages of prefabricated fiber posts include good aesthetics, resistance to corrosion, a modulus of elasticity nearly equal to dentin, and adhesive bonding to the root canal wall surface. This adhesive bond creates a good bond with the tooth structure and also improves the monoblock properties due to the use of the same material. After the post is placed into the root canal, a crown is placed to perfect the shape of the root canal crown. This case report describes the steps involved in installing a prefabricated post and crown on a tooth after root canal treatment. The first visit involved gutta-pertussis reduction with gates, followed by root canal widening. A trial post was then placed, followed by post cementation and core fabrication. Impressions and temporary crowns were made after the cores were made. The patient was instructed to return once the zirconia crown was finished, and it was inserted immediately. Following treatment, it was concluded that prefabricated posts, followed by zirconia crowns, can be placed after root canal treatment in anterior teeth with significant crown structure loss